Mixed‐methods Evaluation of the Good Behaviour Game in English Primary Schools. (29th February 2016) - Coombes, Lindsey; Chan, Gail; Allen, Debby; Foxcroft, DAVID R.
Abstract: Inclusivity of all children in education and within educational settings is an important value and goal. Yet, where settings and practices are not oriented for inclusivity and engagement, some children can struggle with academic tasks and are often marginalised and exhibit disruptive behaviours. The study reported here addresses the social nature of school as a community for learning through a mixed‐methods concurrent triangulation evaluation of the implementation of the Good Behaviour Game (GBG) in six primary (elementary) schools with 10 classes and 222 children in Oxfordshire, England. The Teacher Observation of Classroom Adaptations ‐ Revised (TOCA‐R) was administered in individual interviews with class teachers. Additionally, individual semi‐structured interviews were conducted with teachers, coaches and head teachers ( n = 22). In a pre–post design, improvements in child adaptation were observed on all TOCA‐R subscales. In an integrative analysis that brought together quantitative and qualitative findings, pupil improvement was identified in three major areas: inclusion and social participation, behaviour, and concentration. Interview results also highlighted the substantial practical challenges associated with implementing and using the GBG in schools in the UK. Overall, the results of this study support the idea that social relationships within the school community, between pupils and between pupils and teachers, provide an important context for learning and social development. Copyright © 2016 John Wiley & Sons, Ltd.